Environmental Cost Disclosure for Promoting Green Economy Implementation in Situ Ciburuy Tourism - Ramdhani, Alfian; Kesumo Wardhani, Nurhastuty (MediaTrend, 2025)
This study examines environmental costs in the Situ Ciburuy tourist area, West Bandung, as part of efforts to promote the adoption of the green economy concept. Using a qualitative descriptive approach with a field study method, the researcher serves as the primary instrument for data collection. Triangulation techniques are employed to integrate multiple data sources, ensuring a more comprehensive analysis. The study gathers both primary and secondary data, with key informants including tourism managers at Situ Ciburuy and members of the local community.Findings reveal that environmental costs at Situ Ciburuy are recorded alongside other expense components in profit and loss financial statements. These costs mainly arise from waste management activities, such as garbage disposal and aquatic ecosystem conservation, and are documented in operational reports. The disclosure of environmental costs provides insight into expenditures on eco-friendly initiatives that tourism managers must undertake. Transparent reporting of these expenses enhances awareness of the importance of investing in sustainable practices aligned with green economy principles.This research aims to support the development of sustainable tourism at Situ Ciburuy and serve as a reference for other tourism managers seeking to implement the green economy concept more effectively.